2016
DOI: 10.1139/apnm-2015-0235
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of muscle stretching on physical performance, range of motion, and injury incidence in healthy active individuals: a systematic review

Abstract: Abstract:Recently, there has been a shift from static stretching (SS) or proprioceptive neuromuscular facilitation (PNF) stretching within a warm-up to a greater emphasis on dynamic stretching (DS). The objective of this review was to compare the effects of SS, DS, and PNF on performance, range of motion (ROM), and injury prevention. The data indicated that SS-(-3.7%), DS-(+1.3%), and PNF-(-4.4%) induced performance changes were small to moderate with testing performed immediately after stretching, possibly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
578
6
50

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 510 publications
(651 citation statements)
references
References 118 publications
(179 reference statements)
17
578
6
50
Order By: Relevance
“…Stretching is a strategy commonly employed in both training and rehabilitation programs [2] and it is used often in warm-up routines [6]. Nevertheless, a considerable amount of evidence in the last decade has shown that stretching prior to activity may impair performance [7][8][9]. Hence, elongating a muscle prior to tasks that require maximal performance has been discouraged.…”
Section: Introductionmentioning
confidence: 99%
“…Stretching is a strategy commonly employed in both training and rehabilitation programs [2] and it is used often in warm-up routines [6]. Nevertheless, a considerable amount of evidence in the last decade has shown that stretching prior to activity may impair performance [7][8][9]. Hence, elongating a muscle prior to tasks that require maximal performance has been discouraged.…”
Section: Introductionmentioning
confidence: 99%
“…In paper 1, improvements in both the STRENGT and STRETCH group were found. In addition, stretching improves range of motion due to increased flexibility in muscles and tendons, as well as neural adaptations leading to an improved stretch tolerance [150]. Hence, even if stretching earlier has been interpreted to not be beneficial for chronic pain conditions [39], there is interesting to speculate about possible physiological effects as results of stretching exercise in painful muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Increased muscle tension in chronically painful muscles has in fact been reported earlier [228,229], and muscle tension might enhance the nociceptive activity and thus, in a sensitized nervous system lead to increased pain perception. If stretching diminish the nociceptive activity [150,151] by reducing the muscle tension, stretching could consequently possibly lead to decreased pain perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations